2018
DOI: 10.4103/ijpsym.ijpsym_158_18
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Psychiatric Comorbidity in Infertile Women - A Cross-Sectional Hospital Based Study

Abstract: Background and Aim: In Asian countries, child bearing is a social obligation. Experience of infertility profoundly affects the personal well-being of women. Women with infertility are at a higher risk of anxiety, depression, and Intimate partner violence (IPV). In this background the present study was carried out to determine IPV and psychiatric comorbidity in women with infertility. Methods: Hundred consecutive women with primary infertility in the age group of 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“… 16 The overall prevalence of violence against infertile women was obtained from 15 studies considered for the current evaluation with a sum total of 4,394 participants. 15 , 16 , 18 , 20 , 27 , 28 , 32 35 , 38 , 39 , 43 , 45 , 46 A sub-total of 12 studies with 3,872 participants reported psychological and emotional violence and this type of violence was the most common compared to the rest. 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 The overall prevalence of violence against infertile women was obtained from 15 studies considered for the current evaluation with a sum total of 4,394 participants. 15 , 16 , 18 , 20 , 27 , 28 , 32 35 , 38 , 39 , 43 , 45 , 46 A sub-total of 12 studies with 3,872 participants reported psychological and emotional violence and this type of violence was the most common compared to the rest. 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 , 18 , 20 , 27 , 28 , 32 35 , 38 , 39 , 43 , 45 , 46 A sub-total of 12 studies with 3,872 participants reported psychological and emotional violence and this type of violence was the most common compared to the rest. 15 , 16 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 A total of 14 studies with 4,394 participants reported the presence of or increase in physical violence. 15 , 16 , 18 , 20 , 27 , 28 , 30 , 32 35 , 39 , 45 , 46 Also, 11 studies with 3,460 participants reported sexual violence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IPV was found to be significantly higher in those with psychiatric comorbidity. [8] The relationship between IPV and depression is more likely to be bidirectional, whereas that between IPV, infertility, and psychiatric comorbidity is more complex and confounded by various sociodemographic and clinical variables. The role of stress-because of stressors such as IPV-in inducing neuroendocrine changes, which could, in turn, lead to infertility and psychiatric morbidity, needs further exploration.…”
Section: Guest Editorialmentioning
confidence: 99%
“… 2 Many studies have investigated the emotional stress related to infertility. 3 , 4 There have been reports of adverse effects on the psychological health of women who receive infertility treatment, including a high state of anxiety and a tendency to develop depression. 5 Pregnancy after infertility treatment brings increased anxiety and psychological stress to the mother about the outcome of the pregnancy and the care of the precious newborn.…”
mentioning
confidence: 99%